An Extremely Rare Case of Gastroptosis Treated Successfully with Itopride in a Patient with Parkinson’s Disease - Kübra Yildiz Cömert; Alper Tuna Güven (Nigerian Postgraduate Medical Journal)
A rare condition known as gastroptosis causes the major curvature of the stomach to shift downward and towards the pelvis. While some are asymptomatic, others experience symptoms. Cross-sectional imaging, or barium X-rays, are diagnostic. The main treatment strategy is conservative, and gastric motility stimulants, including dopamine antagonists, are the mainstay of the treatment. Herein, we describe an elderly patient with multimorbidity, polypharmacy and Parkinson’s disease admitted to our clinic with nausea, vomiting and unintentional weight loss complaints who was diagnosed with gastroptosis and treated successfully with itopride, a dopamine antagonist, without worsening Parkinson’s disease. This exceedingly rare condition should be kept in mind in patients with gastrointestinal symptoms whose initial diagnostic search is unrevealing. Although the presence of Parkinson’s disease casts doubt on the use of dopamine antagonists, itopride has a very low central nervous system (CNS) pass and CNS-related side effects. Moreover, the absence of effective and safe measures other than dopaminergic antagonists and interventional methods renders their use compulsory.